Relaksasi Benson Untuk Durasi Tidur Pasien Penyakit Jantung Koroner - Muliantino, Mulyanti Roberto; Herawati, Tuti; Masfuri, Masfuri (Jurnal Endurance, 2018)
Coronary Arterial Disease (CAD) is one of cardiovaskular disease that remain leading cause death and disability. Short sleep duration is the major symptoms in patients with CAD, during recovery period after cardiac events and during cardiac rehabilitation. Benson’s relaxation is one of relaxation as modalities therapy to increase sleep duration, however few studies related to this technique in planned intervention. This study was to measured the effectiveness of Benson’s relaxation in short sleep duration of CAD patients during cardiac rehabilitation. It was a quasi experimental pretest posttest control group design. This study included 29 respondens in Dr.M.Djamil Hospital were assigned to intervention group which receiving Benson’s relaxation technique (n=15) and control group with routine care (n=14). Benson’s relaxation technique was administered for 5 days 2 times a day, each 20 minutes to intervention group. Short sleep duration was measured using sleep diary (self report). The result indicated significant increasing in mean of  sleep duration  before and after Benson’s relaxation in intervention group (p value < 0,001). The study concluded that Benson’s relaxation technique is an effective non-pharmacological intervention to increase sleep duration in CAD patients.Penyakit jantung koroner menjadi masalah kardiovaskular yang mengakibatkan angka mortalitas yang tinggi. Durasi tidur pendek termasuk salah satu keluhan utama pasien penyakit jantung koroner pada masa recovery setelah serangan dan menjalani rehabilitasi fase 2. Relaksasi Benson merupakan teknik relaksasi sebagai terapi modalitas untuk mengurangi keluhan durasi tidur pendek, namum belum banyak penelitian terkait intervensi ini. Penelitian ini bertujuan untuk mengidentifikasi pengaruh relaksasi Benson terhadap durasi tidur pasien penyakit jantung koroner yang menjalani rehabilitasi fase 2. Penelitian ini menggunakan desain Quasi Eksperimen dengan pendekatan control group pretest posttest design pada 29 responden di RSUP. Dr.M.Djamil Padang yang dibagi dalam dua kelompok (kelompok intervensi dan kelompok kontrol). Hasil penelitian menunjukan ada perbedaan rerata durasi tidur yang signifikan antara sebelum dan setelah dilakukan intervensi relaksasi Benson pada kelompok intervensi (p value < 0,001). Simpulan hasil penelitian ini dapat menjadi salah satu terapi modalitas bagi perawat untuk mengatasi masalah durasi tidur pendek pada pasien penyakit jantung koroner.